RETRACTED: Identification of Novel SCN5A Single Nucleotide Variants in Brugada Syndrome: A Territory-Wide Study From Hong Kong - Tse, Gary; Lee, Sharen; Liu, Tong; Yuen, Ho Chuen; Wong, Ian Chi Kei; Mak, Chloe; Mok, Ngai Shing; Wong, Wing Tak (Frontiers in Physiology, 2020)
Background The aim of this study is to report on the genetic composition of Brugada syndrome (BrS) patients undergoing genetic testing in Hong Kong. Methods Patients with suspected BrS who presented to the Hospital Authority of Hong Kong between 1997 and 2019, and underwent genetic testing, were analyzed retrospectively. Results A total of 65 subjects were included (n = 65, 88% male, median presenting age 42 [30–54] years old, 58% type 1 pattern). Twenty-two subjects (34%) showed abnormal genetic test results, identifying the following six novel, pathogenic or likely pathogenic mutations in SCN5A: c.674G > A, c.2024-11T > A, c.2042A > C, c.4279G > T, c.5689C > T, c.429del. Twenty subjects (31%) in the cohort suffered from spontaneous ventricular tachycardia/ventricular fibrillation (VT/VF) and 18 (28%) had incident VT/VF over a median follow-up of 83 [Q1–Q3: 52–112] months. Univariate Cox regression demonstrated that syncope (hazard ratio [HR]: 4.27 [0.95–19.30]; P = 0.059), prior VT/VF (HR: 21.34 [5.74–79.31; P < 0.0001) and T-wave axis (HR: 0.970 [0.944–0.998]; P = 0.036) achieved P < 0.10 for predicting incident VT/VF. After multivariate adjustment, only prior VT/VF remained a significant predictor (HR: 12.39 [2.97–51.67], P = 0.001). Conclusion This study identified novel mutations in SCN5A in a Chinese cohort of BrS patients.